Statistical Analysis On The Effect Of Machining Conditions Towards Surface Finish During Edge Trimming Of Carbon Fiber Reinforced Plastics (CFRP) - Sundi, Syahrul Azwan; Raja Abdullah, Raja Izamshah; Kasim, Mohd Shahir; Jaafar, Mohd Fairuz; S. Ding, S. Ding (Penerbit UniMAP, 2020)
The main aim of this work was to investigate the effect of machining conditions namely cutting speed (Vc) and feed per tooth (fz) towards the surface finish during the edge trimming process on a specific CFRP material. The range of cutting speed (Vc) applied was 50m/min (low), 100 m/min (middle) and 150 m/min (high) whilst for the feed per tooth (fz); 0.05 mm (low), 0.10 mm (middle) and 0.15 mm (high). The CFRP panel is measured 3.25 mm in thickness and has 28 plies in total. Router or burr tool made of uncoated tungsten carbide with a diameter of 6.35 mm is used to perform the edge trimming process. The Taguchi technique has been adopted to plan the overall experimental process. Surface roughness measurement was taken using Mitutoyo Surftest SJ-410 and optical microscope Nikon MM-800 is utilized to further observe the quality of the trimmed surfaces. From the ANOVA analysis, both factors namely cutting speed, Vc and feed per tooth, fz indicated a significant result towards the surface finish of the trimmed surfaces. The result is supported by the observation via optical microscopy which clearly exhibits uncut fibers, fiber pull-out and matrix degradation conditions. Detailed results are elaborated and discussed further in this paper.